In the balance of power : independent Black politics and third-party movements in the United States - Ali, Omar H. (Omar Hamid) (Ohio University Press, 2020)
"Reveals the multiple independent political tactics and strategies that African Americans have used to expand democracy and uphold civil and political rights since the founding of the nation. This new edition of Ali's groundbreaking narrative includes an epilogue by independent political analyst and leader Jacqueline Salit. New material addresses the historic presidencies of both Barack Obama and Donald Trump, as well as the rising tide of independent and anti-party sentiments"--